Analysis of the effectiveness of decisions made in the occupational risks assessment on the examples of aviation incidents - Tsopa, Vitalii; Borodina, Nataliya; Cheberyachko, Serhiy; Deryugin, Oleg; Lantukh, Dmytro; Sushko, Nadia (Social Development and Security, 2024)
Purpose: is to analyze the effectiveness of decision-making in risk assessment in complex situations. Method: professional risk management model. Findings: The article analyses the cause-and-effect relationships of five different incidents (aircraft crashes) with the main hazard of “height”, considering the hazardous factors, unsafe acts and inaction that led to significant material losses and human casualties in some cases, and in others, because of the available opportunities, to minimise them, which became the basis for analysing the management decisions made by aircraft captains. The article analyses the effectiveness of risk assessment decisions and identifies the best options for making decisions regarding unacceptable risks. Practical value of the research: A matrix for assessing the consequences of material losses because of risk assessment decisions is proposed, which shows that the options for decisions without consequences occur when the risk is avoided or transferred to others. Originality: Justification of management decisions based on risk assessment, considering the four basic options for risk evaluation: acceptance, reduction, avoidance, and transfer. Future research. In the future, it is important to conduct research based on game theory to make decisions in the safety sector, and to use artificial intelligence to speed up the process of identifying the desired result. Papertype: practical.